Networks Security models Scalability Analysis - Kamal Aldin Yousif Yaseen (Journal of engineering sciences and information technology, 2019)
There is an emerging scalability problem with existing security models as the size of the networked systems becoming larger, especially when analyzing all possible attack scenarios. presented the worst case computational complexity analyses based on fully connected topology, but real life networked systems run on various network topologies, and other factors that affect the overall performances of security models. In this research, the scalability of existing security models is evaluated and compared with the HARM in realistic scenarios. Two main tasks in this research are (1) formulating key questions that need to be answered to assess the scalability of security models, and (2) evaluate and compare the scalability of security models using simulations.